Genotoxicity of Marijuana in Mono-Users - Fabian-Morales, Eunice; Fernández-Cáceres, Carmen; Gudiño, Adriana; Andonegui Elguera, Marco A.; Torres-Arciga, Karla; Escobar Arrazola, Marco Armando; Tolentino García, Laura; Alfaro Mora, Yair E.; Oliva-Rico, Diego A.; Cáceres Gutiérrez, Rodrigo E.; Domínguez Ortíz, Julieta; Castro Hernández, Clementina; et al. (Frontiers in Psychiatry, 2021)
Marijuana (Cannabis sp.) is among the most recurred controlled substances in the world, and there is a growing tendency to legalize its possession and use; however, the genotoxic effects of marijuana remain under debate. A clear definition of marijuana’s genotoxic effects remains obscure by the simultaneous consumption of tobacco and other recreational substances. In order to assess the genotoxic effects of marijuana and to prevent the bias caused by the use of substances other than cannabis, we recruited marijuana users that were sub-divided into three categories: 1) users of marijuana-only (M), 2) users of marijuana and tobacco (M+T) and 3) users of marijuana plus other recreative substances or illicit drugs (M+O), all the groups were compared against a non-user control group. We quantified DNA damage by detection of γH2AX levels and quantification of micronuclei (MN), one of the best-established methods for measuring chromosomal DNA damage. We found increased levels of γH2AX in peripheral blood lymphocytes from the M and M+T groups, and increased levels of MNs in cultures from M+T group. Our results suggest a DNA damage increment for M and M+T groups but the extent of chromosomal damage might be related to the compounds found in tobacco. We also observed an elevated nuclear division index in all marijuana users in comparison to the control group suggesting a cytostatic dysregulation caused by cannabis use. Our study is the first in Mexico to assess the genotoxicity of marijuana in mono-users and in combination with other illicit drugs.